Le stade de Wimbledon - Almaric, Mathieu, 1965-; Balibar, Jeanne, 1968-; Gorintin, Esther; Prucnal, Anna; Del Giudice, Daniele (Gemini Films, 2001)
A young woman investigates a writer, who died without having published anything. During her trip, which takes her from Trieste to London, she meets relatives and friends of the deceased. --